2008
DOI: 10.1080/10428190701824544
|View full text |Cite
|
Sign up to set email alerts
|

Aurora A kinase RNAi and small molecule inhibition of Aurora kinases with VE-465 induce apoptotic death in multiple myeloma cells

Abstract: The expression of RHAMM and other centrosome-associated genes are known to correlate with the extent of centrosome amplification in multiple myeloma, and with poor prognosis. RHAMM has a significant interaction with TPX2, a protein which regulates the localization and action of Aurora A kinase (AURKA) at the spindle poles. AURKA is known to be a central determinant of centrosome and spindle function and is a target for cancer therapy. Given these observations, we investigated the role of Aurora kinases as ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
46
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 29 publications
7
46
0
Order By: Relevance
“…However, both kinases have different effects on the mitotic process [18]. Numerous inhibitors have been developed against both classes of kinases and some aurora kinase inhibitors have been shown to have effects on multiple myeloma [25][26][27][28][29][30][31]. Indeed, ENMD-2076 is currently undergoing phase I trial [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, both kinases have different effects on the mitotic process [18]. Numerous inhibitors have been developed against both classes of kinases and some aurora kinase inhibitors have been shown to have effects on multiple myeloma [25][26][27][28][29][30][31]. Indeed, ENMD-2076 is currently undergoing phase I trial [18].…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] Because high Aurora-A gene expression has been correlated with centrosome amplification and a worse prognosis in MM, inhibition of Aurora-A may prove to be therapeutically beneficial. 2,6,9,[19][20][21][22][23][24] Recently, we and others have shown that inhibition of Aurora-A kinase gene expression in MM cells by RNAi induces apoptosis Submitted December 18, 2009; accepted March 31, 2010. Prepublished online as Blood First Edition paper, April 9, 2010; DOI 10.1182 DOI 10.…”
mentioning
confidence: 99%
“…6,19,24,27,33 A recent analysis showed no association between genetic instability and expression of Aurora kinases in MM. 9,20 In this preclinical study, we investigated the anti-MM activity of MLN8237, an orally available novel small molecule selective inhibitor of Aurora-A kinase. Aurora-A kinase activity is necessary for proper mitotic progression 11,12,26 : expression of Aurora-A kinase protein peaks during mitosis and is activated by phosphorylation at Thr288.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In pacreatic cancer, colorectal cancer, non-small cell lung cancer and multiple myeloma cell lines, specific suppression of expression of Aurora A lead to G2-M arrest and apoptosis, and can enhance chemosensitivity and radiation response (18,37,38). It is reported that Aurora A activates Akt-induced cell survival and chemoresistance in a p53-dependent manner in ovarian cancer cells (39).…”
Section: Discussionmentioning
confidence: 99%